The Relationship Between Technostress and Health Behavior Among University Professors at the University of Algiers 2 - Assia Attar (Pegem Journal of Education and Instruction, 2026)
The present study aimed to identify thesources of technostress among university professors at the University of Algiers 2 and toexamine its relationship with their level ofhealth behavior practice.